Evolution of the Economy Towards Information Society - Olszewski, Jerzy (Studia Oeconomica Posnaniensia, 2013)
Abstract: This article consists of four parts. The first chapter describes five phases of information society development, with an emphasis on the concept of a knowledge-based economy with the key role of science. The second part of the article is devoted to the definition of an information society and presents several well-known definitions; however, at this point it is difficult to determine which of them best describes the analysed phenomenon since each presents it within a specific economic and social context. In addition, the services rendered to citizens by means of new IT systems are described here. The next - third - part focuses on the essence of an information society, paying particular attention to its connections with Information and Communications Technology (IC T), economic growth and social development. It describes various forms of services provided in an electronic form, and analyses the use of Internet services by the global population and the use of IC T and Internet services in the European Union. Also, the analysis includes the structure of services available to citizens and enterprises on e-administration platforms. In the final part of the study the author presents the impact of IT systems on the shaping of new forms of employment and jobs, differentiated qualitatively in terms of content. The article closes with some final comments, in which the above mentioned issues are summarised.